Gamma-Ray Bursts at TeV Energies: Observational Status - Koji Noda; Robert Daniel Parsons (Galaxies, 2022)
Gamma-ray bursts (GRBs) are some of the most energetic events in the Universe and are potential sites of cosmic ray acceleration up to the highest energies. GRBs have therefore been a target of interest for very high energy gamma-ray observatories for many years, leading to the recent discovery of a number of bursts with photons reaching energies above 100 GeV. We summarize the GRB observational campaigns of the current generation of very high energy gamma-ray observatories as well as describing the observations and properties of the GRBs discovered so far. We compare the properties of the very high energy bursts to the total GRB distribution and make predictions for the next generation of very high energy gamma-ray observations.